Blockchain technology potential in halal industry - Halizan, Mohmood (2021)
KUANTAN, 28 July 2021 - The Centre of Industry and Community Network (ICoN), Universiti Malaysia Pahang (UMP), together with the German Alumni Association of Malaysia (GAAM), Blockworq Sdn. Bhd. and Maishince Academy organised a Professional Talk Series Webinar Forum Series 2 titled ‘Facts, Myths and Potential of Blockchain Technology in the Halal Industry’ to unravel the misunderstandings surrounding the issue of the use of blockchain technology in the halal industry.